Factors associated with sarcopenia and undernutrition in older adults - Sousa Santos, AR (2019)
Aim: The aim of this study was to describe sarcopenia frequency, to identify the factors associated with sarcopenia and undernutrition, and to evaluate their coexistence. Methods: A total of 1500 Portuguese older adults aged 65 years from the Nutrition UP 65 study were evaluated using a cross-sectional analysis. Sarcopenia was defined according to the European Working Group on Sarcopenia in Older People (EWGSOP)2 guidelines (2018), using anthropometric measures. Undernutrition status was evaluated by Mini-Nutritional Assessment-Short Form. Results: Sarcopenia frequency was 4.4% (n = 66). Sarcopenia coexists with undernutrition or undernutrition risk in 1.5% of this sample. In the multivariate analysis, sarcopenia was directly associated with age >75 years (odds ratio (OR): 2.14; 95% confidence interval (CI): 1.193.84), undernutrition or undernutrition risk (OR: 1.86; 95% CI: 1.013.43) and inversely associated with male gender (OR: 0.52; 95% CI: 0.290.97), overweight (OR: 0.24; 95% CI: 0.130.42) or obesity (OR: 0.02; 95% CI: 0.010.09) and moderate alcohol consumption (OR: 0.47; 95% CI: 0.240.90). Undernutrition or undernutrition risk was associated with a poor or very poor self-perception of health status (OR: 3.53; 95% CI: 2.325.37), a low physical activity level (OR: 1.74; 95% CI: 1.232.47), sarcopenia (OR: 1.85; 95% CI: 1.023.36), and being overweight (OR: 0.40; 95% CI: 0.270.59) or obese (OR: 0.43; 95% CI: 0.280.65). Conclusions: The majority of the older adults presented low muscle strength (probable sarcopenia), but only a small number had concomitantly low muscle quantity or quality (sarcopenia). Coexistence between these conditions is low which reinforces the need to assess them both individually during geriatric assessment. (c) 2019 Dietitians Association of Australia